A study of postnatal assessment of gestational age of neonates by new Ballards and Parkins score - Mehta, Vivek R.; Parmar, Hardik R.; Khandwala, Amola B.; Kakkad, Khyati M.; Vekaria, Vaidehi V.; Bhatt, Jaladhi V. (International Journal of Contemporary Pediatrics, 2021)
Background: The aim, of the study was to find the correlation between new Ballard score and Parkin’s score and whether they correlate with obstetric gestational age estimated by LMP and/or 1st-trimester USG. Methods: A cross-sectional clinical study for 6 months duration was carried out at tertiary care NICU and postnatal ward of a teaching hospital. Any intramural neonate admitted in NICU and neonates examined after randomized selection in postnatal ward within the first 24 hours of life were included in the study after written informed consent. Their demographic profile was documented using preset Performa and gestational age was assessed using both New Ballard score and Parkins score. Results: Total 387 new-borns were screened with mean age of 12.86±11 hours. Out of which 209 (54.0%) were males and 178 (46.0%) were females. The 259 (66.0%) new-borns were normal vaginal delivered and 128 (33.0%) new-borns were delivered by caesarean section. In the study it was found that the obstetric gestational age strongly correlates to gestational age by new Ballard score (r=0.880, p<0.001), and to gestational age by Parkins score (r=0.880, p<0.001). The gestational age by new Ballard score also strongly correlates to gestational age by Parkins score (r=0.937, p<0.001). Scatter diagram shows that there is strong positive linear correlation between gestational age assessed by LMP and NBS. While that gestational age accessed by Parkins having weak positive relationship compared to NBS. Conclusions: New Ballard score predicts new-born gestational age better in preterm and term new-borns, but Parkin’s Score, being simpler assessment method, takes very less time and has the advantage of no subjective neurological criteria and lesser interpersonal variation.